Authority, autonomy, and the archaeology of a Mississippian community - Nelson, Erin S. (Ripley P. Bullen series., 2020)
This book is the first detailed investigation of the important archaeological site of Parchman Place in the Mississippi Delta, a defining area for understanding the Mississippian culture that spanned much of what is now the United States Southeast and Midwest before the fifteenth century.